Combined Femtosecond Laser-Assisted Cataract Surgery and 27-Gauge Transconjunctival Sutureless Vitrectomy. (23rd March 2020) - Yılmaz, Sami; Avcı, Remzi; Mavi Yıldız, Ayşegül
Abstract : Purpose . To report the outcomes of combined surgery using femtosecond laser-assisted cataract surgery (FLACS) and sutureless 27-gauge pars plana vitrectomy with intravitreal tamponade. Methods . This retrospective clinical study involved 23 eyes of 23 patients on whom combined vitreoretinal surgery was performed. Patients were initially given the femtosecond laser treatment that was performed after selection of capsulotomy and lens fragmentation patterns. The capsulotomy diameter was chosen as 4.9 mm in all patients. After the femtosecond laser, the sutureless phacovitrectomy procedure was performed. At the end of surgery, perfluoropropane or sterile air tamponade was applied. Results . The mean age of patients was 66.43 ± 7.61 (range, 54–83) years. Fifteen patients were females (65.2%). The mean follow-up was 16.09 ± 4.71 (range, 9–25) months. The most common surgical indication was epiretinal membrane (65.3%). The mean preoperative best-corrected visual acuity (BCVA) was 0.71 ± 0.44 (range, 1.7–0.3) logMAR, and the mean postoperative BCVA at 6 months was 0.16 ± 0.14 (range, 0.4–0) logMAR p < 0.001 . The mean target sphere refractive error was −0.24 ± 0.16 (range, −0.50–0.11) D, and the mean postoperative spherical equivalent refractive error was −0.14 ± 0.39 (range, −1.00–0.50) D at 6 months p = 0.196 . All intraocular lenses (IOLs) remained well centered in the capsular bag during surgery and follow-up. There was no iris capture, posterior synechiae, capsular opacification, or pseudophakic cystoid macular edema. The only complication related to femtosecond laser was two cases of subconjunctival haemorrhage related with suction. Conclusions . FLACS is a safe and effective technique providing the advantage of repeatable, precise capsulorhexis shape and size to achieve a well-centered and stable IOL postoperatively. These advantages can certainly improve the results of vitrectomy, especially in gas-filled eyes. FLACS and 27-gauge sutureless combined surgery may be a future trend in appropriate cases.